Critical ‘intercultural awareness’ enhancement: Effects of using asynchronous online discussion with Thai tertiary students - Rajprasit, Krich (Universitas Pendidikan Indonesia, 2020)
In the globalized era, the interaction between people from different cultures increases dramatically. This affects the way the English language is used, and how the language is taught at all levels of education. Regarding this, English language teachers are recommended to reconsider their current classroom practices in light of the above issue. One basic recommendation is to incorporate other cultural aspects besides just the American and British models commonly used today. However, research on developing learners’ critical ‘intercultural awareness’ (ICA) is rare in the literature, particularly regarding the use of asynchronous online discussion (AOD) at the Thai tertiary level. This study aimed to investigate the AOD use to develop critical ICA and to examine the effects of such AOD use on the learning of Thai students. Twelve ICA-enhanced AOD tasks were developed as instructional instruments. From these, research instruments were developed, including a pretest, a posttest, a self-reported questionnaire, and an in-depth interview. Two groups of Thai students with different English proficiency levels were selected to join the experiment, classified as a high proficiency (HP) group and a low proficiency (LP) group. After AOD implementation, their performances were assessed. Findings revealed improvements in the performances of both groups, with the mean posttest scores being higher in both groups, with the HP group demonstrating better performance. In addition to posttest scores, the participants provided positive perceptions of the AOD tasks, with no significant differences in the perceptions between groups. The interview responses revealed the students’ perceptions that the AOD tasks were challenging, but provided them with an opportunity to think critically about the culturally related questions. This study highlights the benefits of developing critical ICA in an ELT classroom with the AOD use, especially HP students, even though it may not work very well with LP students.